Peran Moral Engagement Memediasi Antara Attitude Dan Intention to Corruption pada Mahasiswa - Zeverina Nur Alifah Zahra; Etik Darul Muslikah; Eben Ezer Nainggolan (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2025)
Abstract Corruption is a serious problem that not only undermines governance but has also spread to various sectors, including higher education. Students, as agents of change, even show a permissive attitude toward corrupt behavior from their college days. This study aims to examine the relationship between attitude and intention to engage in corruption, as well as the role of moral engagement as a mediator among students. This study employs a quantitative approach with a correlational design. The subjects of this research are active students in Surabaya, with a population of 300,031 and a sample of 358 students selected using convenience sampling. Data were analyzed using mediation regression with the assistance of SPSS software and the PROCESS Macro Model 4. The results of the study indicate that attitudes toward corruption have a positive and significant relationship with the intention to engage in corruption. Additionally, moral engagement was found to partially mediate this relationship Keywords: Attitude, Intention to Corruption, Moral Engagement Abstrak Korupsi merupakan permasalahan yang serius tidak hanya merusak tata kelola pemerintahan, tetapi juga telah merambah di berbagai sektor, termasuk perguruan tinggi. Mahasiswa sebagai agen perubahan bahkan menunjukkan kecenderungan permisif terhadap perilaku koruptif sejak di bangku kuliah. Kajian ini bertujuan untuk menguji hubungan antara attitude dan intention to corruption, serta peran moral engagement sebagai mediator pada mahasiswa. Kajian ini menggunakan pendekatan kuantitatif dengan desain korelasional. Subjek dalam penelitian ini adalah mahasiswa aktif di Surabaya dengan jumlah populasi 300.031 dan sampel sebanyak 358 mahasiswa yang dipilih menggunakan teknik convience sampling. Data dianalisis menggunakan regresi mediasi melalui bantuan perangkat lunak SPSS dan PROCESS Macro Model 4. Hasil penelitian menunjukkan bahwa sikap terhadap korupsi memiliki hubungan positif dan signifikan dengan niat untuk melakukan korupsi. Selain itu, moral engagement terbukti memediasi secara parsial hubungan tersebut. Kata kunci: Attitude, Intention to Corruption, Moral Engagement